Coronavirus disease (Covid-19): How does the exercise practice in active people with type 1 diabetes change? A preliminary survey - Assaloni, Roberta; Pellino, Vittoria Carnevale; Puci, Mariangela V.; Ferraro, Ottavia E.; Lovecchio, Nicola; Girelli, Angela; Vandoni, Matteo (Diabetes research and clinical practice, 2020)
•An adequate Physical Activity level can help patients to maintain good glycemia control.•People with type 1 diabetes reduced their Physical Activity level during quarantine.•People with type 1 diabetes increased mean glycemic values.•Specific suggestions on home training manage should be given to people with type 1 diabetes. Coronavirus disease (Covid-19) could lead persons with pre-existing medical conditions to severe respiratory infections. The Italian Government introduced quarantine to limit viral transmission. This measure could lead people with type 1 diabetes (PWT1D) to disrupt daily care routine including PA practice with difficulties in glycemia management. This study aims to explore PA level in PWT1D before and during quarantine and to describe variation in glycemia values. An online survey investigating medical factors and the perceived and PA level in pre-established period before and after the introduction of quarantine was developed. Comparison between pre and post quarantine was assessed by Wilcoxon Signed Ranks test for continuous variables. A total of 154 subjects satisfied the eligibility criteria (54.5% males, 44.8 ± 12.5 years). We found a decrease of PA level (Godin Scale Score 25 ± 1.7vs38.6 ± 1.7 points), steps number and minutes of exercise (respectively 12.606 ± 5026vs4.760 ± 3.145 and 66±4 vs 38±3) and an increase of glycemia values (142.1 ± 25.4 mg/dLvs150.8 ± 29.4 mg/dL). PWT1D reported a decrease in exercise and worst glycemia. Although PWT1D tried to remain active, their PA level was inadequate to prevent glycemia rising. The difficult to maintain a glycemic control could expose patients to diabetes complications and to an higher risk to counteract infections.